Między azylem a więzieniem. Metafora domu w powieściach Dom z witrażem Żanny Słoniowskiej i Dim dla doma Viktorii Ameliny - Jakubowska-Krawczyk, Katarzyna; Zambrzycka, Marta (Przegląd Wschodnioeuropejski, 2022)
In this article we analyse the topos of the home in two novels set in Lviv: “Home for Dom” by Viktoria Amelina and “The house with the Stained-glass Window” by Zhanna Sloniovska. In both of them, the eponymous ‘home/house’ contains family secrets which are meant to be representatives of the Eastern European fate. The metaphor of a home has several meanings in both novels: it refers to an apartment, a home-city (Lviv) and a homeland. On both dimensions, the home has not been presented as stable and unchanging space. It is rather a symbol of transience than permanence. In both novels, the family stories reflect the problems of identity and memory of the inhabitants of modern Ukraine.